Spatial distribution of quasi-biennial oscillations in high-latitude solar activity. Issue 4 (6th May 2020) - Deng, L H; Fei, Y; Deng, H; Mei, Y; Wang, F
ABSTRACT: Quasi-biennial oscillations (QBOs) are considered to be a fundamental mode of solar magnetic activity at low latitudes (≤50°). However, the evolutionary aspect and the hemispheric distribution of solar QBOs at high latitudes (≥60°) are rarely studied. Here, we apply a relatively novel time-frequency analysis technique, called the synchrosqueezed wavelet transform, in order to extract the main components of the polar faculae in the Northern and Southern hemispheres for the time interval from 1951 August to 1998 December. We note the following. (i) Apart from the 22-yr Hale cycle, the 17-yr extended activity cycle and the 11-yr Schwabe cycle, QBOs have been estimated as a prominent time-scale of solar magnetic activity at high latitudes. (ii) The QBOs of the polar faculae are coherent in the two hemispheres, but the temporal (phase) and the spatial (amplitude) variations of solar QBOs occur unevenly on both hemispheres. (iii) For the 11-yr period mode, this begins in the Northern hemisphere three months earlier than in the Southern hemisphere. Moreover, the spatial and temporal distributions of the hemispheric QBOs differ from those of the 11-yr Schwabe cycle mode in the two hemispheres. Our findings could be helpful to improve our knowledge of the physical origin of the spatial distribution of solar QBOs at high latitudes, and could also provide more constraints on solar dynamo models introduced to characterize the different components of the solar magnetic activity cycle.